HEADING AND RECITALS OF VIETNAMESE CONTRACTS IN TRANSLATON INTO POLISH - NOWICKI, Bogdan (Comparative Legilinguistics, 2014)
This paper deals with Vietnamese-Polish and Vietnamese-Polish translation of headings and recitals of contracts. Translation problems in this respect result from historicallyconditioned legal system differences. The recitals of Vietnamese contracts are much more complex than their Polish counterparts. The reasearch methods applied have included: the comparison of comparative texts (called by Neubert parallel texts), the pragmatic model of legal translation of Kierzkowska (2002) and skopos theory of Vermeer (2001). Furthermore, the techniques of providing equivalents for non-equivalent or partially equivalent terminology have been applied as well. The component parts of the recitals of Vietnamese contracts have been discussed. Finally, translative conclusions have been drawn.